Biomechanical comparison among five mid/hindfoot arthrodeses procedures in treating flatfoot using a musculoskeletal multibody driven finite element model. (November 2021) - Peng, Yinghu; Niu, Wenxin; Wong, Duo Wai-Chi; Wang, Yan; Chen, Tony Lin-Wei; Zhang, Guoxin; Tan, Qitao; Zhang, Ming
Highlights: Developing a musculoskeletal multibody driven finite element foot model. Multi-segment foot model was used to drive the foot finite element model. Mid/hindfoot arthrodesis procedures were simulated in both MSK and FE model. Arthrodesis provided stable foot arch and reduced plantar fascia loading. Double and triple arthrodesis increased the loading of the adjacent unfused joint. Abstract: Background and objective: Mid/hindfoot arthrodesis could modify the misalignment of adult-acquired flatfoot and attenuate pain. However, the long-term biomechanical effects of these surgical procedures remain unclear, and the quantitative evidence is scarce. Therefore, we aimed to investigate and quantify the influences of five mid/hindfoot arthrodeses on the internal foot biomechanics during walking stance. Methods: A young participant with flexible flatfoot was recruited for this study. We reconstructed a subject-specific musculoskeletal multibody driven-finite element (FE) foot model based on the foot magnetic resonance imaging. The severe flatfoot model was developed from the flexible flatfoot through the attenuation of ligaments and the unloading of the posterior tibial muscle. The five mid/hindfoot arthrodeses simulations (subtalar, talonavicular, calcaneocuboid, double, and triple arthrodeses) and a control condition (no arthrodesis) were performed simultaneously in the detailed foot multibody dynamics model and FE model. Muscle forces calculated by a detailed multi-segment foot model and ground reaction force were used to drive the foot FE model. The internal foot loadings were compared among control and these arthrodeses conditions at the first and second vertical ground reaction force (VGRF) peak and VGRF valley instants. Results: The results indicated that the navicular heights in double and triple arthrodeses were higher than other surgical procedures, while the subtalar arthrodesis had the smallest values. Five mid/hindfoot arthrodeses reduced the peak plantar fascia stress compared to control. However, double and triple arthrodeses increased the peak medial cuneo-navicular joint contact pressures and peak foot pressures as well as the metatarsal bones stresses. Conclusion: Although mid/hindfoot arthrodesis generally reduced the collapse of medial longitudinal arch and plantar fascia loading during the stance phase, the increased loading in the adjacent unfused joint and metatarsal bones for double and triple arthrodeses should be noted. These findings could account for some symptoms experienced by flatfoot patients after surgery, which may facilitate the optimization of surgical protocols.